Basic steel properties of self-tapping timber screws exposed to cyclic axial loading. (30th June 2019) - Ringhofer, A.; Augustin, M.; Schickhofer, G.
Highlights: First results of self-tapping timber screws failing by high-cycle fatigue. Determination of fatigue strength of self-tapping timber screws by means of "detail category 100". Characterization of fatigue performance with the notch character k SN = 3.87. Description of the fatigue failure mode with microscopic views of fracture pattern. Abstract: Nowadays, modern self-tapping timber screws are frequently applied for various design situations in timber engineering. They are commonly arranged in a way to predominately load them in axial direction, maximizing their load-carrying capacity and stiffness. While the related determination of properties for quasi-static design situations has become a standardized procedure, loading scenarios deviating from these situations have so far been considered insufficiently or not at all. Amongst others, this concerns the fatigue behavior and failure modes, provoked by cyclic loading at stress levels far below the component's quasi-static load bearing capacity. The aim of the research work presented in this article was to fill this gap of knowledge for axially loaded self-tapping screws. Based on theoretical considerations, which indicate that the steel tensile capacity is the decisive factor in the design process, the related experimental investigations were restricted to the product performance of the self-tapping screws themselves. The tests were conducted by means of monotonic and cyclic loading. The stress level σmax as well as the stress ratio R were varied. A selection of failed specimens was additionally examined by means of fractographic scanning electron microscopy (SEM). The gained results allow us to quantify the S/N-relationship in the high-cycle fatigue (HCF) domain in form of the notch character k SN = 3.87 (significant notch) as well as to describe the impact of R on f fat for N = 2·10 6 load cycles by means of "detail category 100" according to Eurocode 3. In addition, the microscopic images help us to understand the specific fatigue fracture mode and that the product-immanent notches and cracks are responsible for the screws' vulnerable behavior in fatigue.